2002
DOI: 10.1073/pnas.052594699
|View full text |Cite
|
Sign up to set email alerts
|

Quantitativein vivoassessment of lung microstructure at the alveolar level with hyperpolarized3He diffusion MRI

Abstract: The study of lung emphysema dates back to the beginning of the 17th century. Nevertheless, a number of important questions remain unanswered because a quantitative localized characterization of emphysema requires knowledge of lung structure at the alveolar level in the intact living lung. This information is not available from traditional imaging modalities and pulmonary function tests. Herein, we report the first in vivo measurements of lung geometrical parameters at the alveolar level obtained with 3 He diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
558
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(592 citation statements)
references
References 27 publications
28
558
2
4
Order By: Relevance
“…[2]), is straightforward and provides regional information, it is now widely recognized that the signal decay due to diffusion in the lungs is multiexponential (51,94), most likely due to multiple scales of restricted diffusion within the lungs (92). Consequently, new directions in this very promising area incorporate multiple b-value measurements using Carr Purcell Meiboom Gill (CPMG) pulse sequences (95) and diffusion tensor imaging combined with modeling (92).…”
Section: Dw Imaging Of Lung Micro-structurementioning
confidence: 99%
See 1 more Smart Citation
“…[2]), is straightforward and provides regional information, it is now widely recognized that the signal decay due to diffusion in the lungs is multiexponential (51,94), most likely due to multiple scales of restricted diffusion within the lungs (92). Consequently, new directions in this very promising area incorporate multiple b-value measurements using Carr Purcell Meiboom Gill (CPMG) pulse sequences (95) and diffusion tensor imaging combined with modeling (92).…”
Section: Dw Imaging Of Lung Micro-structurementioning
confidence: 99%
“…Consequently, new directions in this very promising area incorporate multiple b-value measurements using Carr Purcell Meiboom Gill (CPMG) pulse sequences (95) and diffusion tensor imaging combined with modeling (92). In the future, these techniques may be capable of estimating airway bore size in obstructive lung diseases such as asthma (92). Also, the lower diffusion constant of Xe-129 provides promise for probing smaller scale structures and thus may be more sensitive to disease than DW imaging using HP He-3.…”
Section: Dw Imaging Of Lung Micro-structurementioning
confidence: 99%
“…The attenuation parameter K is thus obtained by fitting the non-diffusion-weighted signals to Eq. [12]. Once K is determined, S DW (n) can be calculated by the following equation: …”
Section: T 1 and Flip Angle-related Attenuation Correctionmentioning
confidence: 99%
“…3 He apparent diffusion is described by two components: (i) a longitudinal diffusion coefficient (D L ), reflective of diffusion along the length of the alveolar duct, and (ii) a transverse diffusion coefficient (D T ), reflective of diffusion perpendicular to the duct. D L measured at a diffusion time of 1.8 ms has been previously shown to be sensitive to emphysema in humans (6,19). Diffusion studies using the cylinder model have also been done using dogs and showed strong correlation to quantitative computed tomography (CT) lung density and volume measurements (13), and histology measurements in rats (9,20) and mice (21).…”
mentioning
confidence: 98%
“…This enables the tracking of disease progression, such as human chronic obstructive pulmonary disease (1,2) and asthma in mouse models (3). 3 He ADC has been shown to be sensitive to changes in terminal airway anatomy, specifically alveolar damage due to emphysema in both humans (1,(4)(5)(6) and animal models (3,(7)(8)(9).…”
mentioning
confidence: 99%